Formação por alternância na licenciatura em educação do campo: possibilidades e limites do diálogo com a pedagogia da alternância - João Batista Begnami (2019)
The objective of this research was to analyze practices and understandings of the Alternation Formation of the Licentiate Course in Field Education (LECAMPO),their limits and possibilities of dialogue with the Alternation Pedagogy. In theoretical terms, the research had as reference on Historical and Dialectical Materialism. The epistemic basis of this referential part of this principle that to achieve the essence of the phenomenon and capture its complexity is necessary to use the entire category, contradiction, mediation and transformative praxis. A knowledge based on the conception of praxis as an educational principle, stress reality and is committed to human emancipation. From this perspective, we seek the fundamental conceptual aspects of Field Education and Alternation Pedagogy, in the context of the Family Educational Centers of Alternation Formation (CEFFAs) and its influences in the implementation of the training of educators in the field, through the Degree of Education Field. The methodology, focused on the qualitative approach, consisted of a literature review to find the state of the art of academic research about Alternating Training in this course, which revealed a field almost absent in the studies. The exploratory research verified the execution of 46 courses in 36 public institutions of higher education in Brazil. The eligibility of LECampo of the Federal University of Minas Gerais wassupported by the criteria: greater experience, pioneering with the first group created in 2005, already conceived by area of knowledge and in Alternance;inspiration or the expansion and institutionalization of the regular offer from (2009). Held 2 focus groups with 12 students from 4 classes from 4 areas: Life and nature Sciences (2013); Language, Art and Literature (2014); Humanities and Social Sciences (2014); Humanities and Social Sciences Social (2015) and Mathematics (2016), and narrative interview with 8 teachers and 5 monitors of said course. The documentary research and the observation, from the insertion in the course, completed the data sources. The result of the research demonstrated that the LECampo does not use the Alternation Pedagogy, but principles of Alternation, which has made possible the construction of a new concept called Alternation Formation. From this construction were abstracted 9 specific pedagogical mediations and 7 Alternating principles that interact in times-spaces, school-community. The strategy of organizing of times and school spaces between school and community revolutionizes the organization of school times; gives opportunityto workers access and retention of higher education; potentiatethe relation theory and practice with the pedagogical mediations mobilized and anti-hegemonic human training practices, intended for a new project of field and society. The contradictory elements identified that do not potentiate the Formation by Alternation are related to the main factors: economic, political, human and pedagogical resources. The results indicate that the Alternance Training in the Degree in Field Education, given its relevance, requires deepening of the research and more studies for its consolidation as a public policy to be expanded at all levels and modalities of Brazilian Education.